A study exploring the relationship between eating disorders and borderline personality disorder - Ortaçgil, Ege (İstanbul Bilgi Üniversitesi, 2009)
Yeme bozukluğu tanısı alan hastaların bir kısmının tedaviye yanıt vermemesi, yeme bozuklukları ve sınır kişilik arasındaki ilişkiye dikkat çekmektedir. Bu hastaların ayrıca tedavi sürecini etkileyen karakter patolojileri olduğu düşünülmektedir. Bu nedenle, bu çalışma özellikle yeme bozuklukları ve sınır kişilik bozukluğunun birlikte gorülme sıklığına ve aralarındaki olası ilişkiye odaklanmıştır.30 yeme bozukluığu, 30 Eksen-1 bozukluğu ve 30 üniversite öğrencisi olmak üzere 90 kişi bu çalışmaya katılmıştır. Sırasıyla, sosyo-demografik ve klinik bilgi formu, Yeme Tutum Testi (EAT-40) ve Borderline Kişilik Envanteri (BPI) kullanılmıştır. Sonuçlar, gruplar arasında BPI'nın farklılık göstermediği yönündedir. Ancak, anoreksiya nervosa tanısı konmuş hastaların % 11.1'inin, tıkanırcasına yeme bozukluğu tanısı almışların % 33.3'ü ve bulimiya nervosa tanısı almışların %41.5'inin borderline kişilik bozukluğu kriterlerini doldurduğu bulunmuştur. Bunun yanı sıra, Eksen-1 tanısı almış hastaların ancak % 20'si bu kriterlere uymaktadır. Regresyon analiz sonuçları, anoreksiya nervosa tansı almış hastalar örneklemden çıkartıldığında, borderline kişilik ve sağlıksız yeme tutum ve davranışları arasında pozitif bir ilişki göstermiştir. Ayrıca, kadınların ve yüksek sosyo-ekonomik düzeydeki katılımcıların daha yüksek oranda sağlıksız yeme tutum ve davranışları sergilediği bulunmuştur. Son olarak, alkol kullanımı, tıkanırcasına yeme ve gece yeme alışkanlıkları olanların daha yüksek oranda borderline özellikler sergiledikleri görülmüştür.

The relationship of eating disorders and borderline personality captures attention as considerable number of eating disorder patients do not respond to treatments as well as the others. It was speculated that some of these patients also suffer from characterological pathology that affects the treatment process and outcome. Therefore, the current study focused primarily on the prevalence of borderline personality disorder among eating disorders and also investigated the possible relationship between borderline features and unhealthy eating attitudes and behaviors. 90 participants; 30 eating disorder patients, 30 patients diagnosed with any other Axis-I disorder, and 30 university students were included to the study. The socio-demographic and clinical forms, EAT-40 (Eating Attitudes Test-40) and BPI (Borderline Personality Inventory) were used as instruments. The results indicated that BPI scores did not differ among eating disorder groups and control groups. Nevertheless, 11.1% of the patients diagnosed with anorexia nervosa, 33.3% of binge-eating disorder, and 41.5% of bulimia nervosa suited the criteria for borderline personality. On the other hand, only 20% of the Axis-I patients received borderline personality disorder diagnosis. Moreover, the regression analysis results yielded a significant positive relationship between borderline features and unhealthy eating attitudes and behaviors, when patients diagnosed with anorexia nervosa was removed from the sample. Additionally, female participants and high SES participants displayed higher unhealthy eating attitudes and behaviors. Finally, alcohol users, binge-eaters and night-eaters displayed significantly higher levels of borderline features.
Yeme bozuklukları ve sınır kişilik bozukluğu ilişkisine dair bir çalışma